Chemotherapy induced gastrointestinal toxicities - Akbarali, Hamid I.; Muchhala, Karan H.; Jessup, Donald K.; Cheatham, Stanley (Advances in cancer research, 2022)
Chemotherapy—induced gastrointestinal dysfunction is a common occurrence associated with many different classes of chemotherapeutic agents. Gastrointestinal toxicity includes mucositis, diarrhea, and constipation, and can often be a dose-limiting complication, induce cessation of treatment and could be life threatening. The gastrointestinal epithelium is rich in rapidly dividing cells and hence is a prime target for chemotherapeutic drugs. The incidence of gastrointestinal toxicity, including diarrhea and mucositis, is extremely high for a wide array of chemotherapeutic and radiation regimens. In fact, 60%–100% of patients on high-dose chemotherapy suffer from gastrointestinal side effects. Unfortunately, treatment options are limited, and therapy is often restricted to palliative care. Therefore, there is a great unmet therapeutic need for preventing and treating chemotherapy-induced gastrointestinal toxicities in the clinic. In this review, we discuss our current understanding of the mechanisms underlying chemotherapy-induced diarrhea and mucositis, and emerging mechanisms involving the enteric nervous system, smooth muscle cells and enteric immune cells. Recent evidence has also implicated gut dysbiosis in the pathogenesis of not only chemotherapy-induced mucositis and diarrhea, but also chemotherapy-induced peripheral neuropathy. Oxidative stress induced by chemotherapeutic agents results in post-translational modification of ion channels altering neuronal excitability. Thus, investigating how chemotherapy-induced changes in the gut- microbiome axis may lead to gut-related toxicities will be critical in the discovery of new drug targets for mitigating adverse gastrointestinal effects associated with chemotherapy treatment.